Modifikasi Skala Self-Efficacy : Analisis EFA dan CFA - Cahyadi, Maskuri Muhammad (Journal of Research and Measurement in Psychology: JPPP, 2025)
This research aims to determine the dimensions of the self-efficacy scale based on Bandura's theory using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) analysis for 151 junior high school (SMP) students. Based on the EFA analysis, it produces three dimensions, namely generality, level and strength. There were 37 scales created by the researchers. However, after carrying out the EFA test, 25 items remained. Items that were dropped were due to factor loading values ​​<0.4. The factors formed from EFA analysis were tested using CFA and formed three factors. From the CFA analysis, the Goodness of Fit results were found to be less than fit, so it was necessary to modify the indicators eight times to improve the fit of the model so that it could be said to be fit based on the chi-square, CFI, TLI, SRMR and RMSEA criteria. The reliability results in the medium category indicate the need for other reliability tests.